Desain Perancangan Akuarium Berbasis Internet Of Things (Iot) - Dody Hidayat; Ramli (Universitas Harapan Medan, 2023)
An aquarium is a vivarium container, typically featuring at least one transparent side, where aquatic animals and plants are kept. Aquariums are usually made of glass or high-strength acrylic plastic in a cubic shape. Fish are widely kept in aquariums, serving not only as pets but also as a source of livelihood. To ensure that fish live healthily and grow rapidly, water conditions must be maintained through proper care. The most critical factors in fish keeping are monitoring water clarity and aquarium lighting. Continuous lighting can lead to algae growth, which negatively affects water clarity. Additionally, leftover fish feed that is not fully consumed can also cause the water to become turbid or dirty. Therefore, an aquarium system design is required to regulate water filling and draining, alongside a light control design utilizing the Internet of Things (IoT). Based on these issues, the author aims to design an IoT-based aquarium equipped with an ultrasonic sensor as the input and two solenoid water valves as the filling and draining faucets (outputs). These inputs and outputs are controlled via a NodeMCU microcontroller equipped with a Wi-Fi network, which can communicate with a smartphone through the Blynk application